Integrative taxonomy reveals cryptic diversity within the Euphorbia nicaeensis alliance (Euphorbiaceae) in the central Balkan Peninsula - Sharovikj Ivanova, Angela; Schönswetter, Peter; Kostadinovski, Mitko; Barfuss, Michael H. J.; Ćušterevska, Renata; Frajman, Božo (Frontiers in Plant Science, 2025)
The Eurasian steppes are the second-largest continuous biome on Earth. Euphorbia glareosa, a member of the Euphorbia nicaeensis alliance, is a widespread species in the macroclimatically defined zonal Pontic steppes and westerly and southerly adjacent extrazonal steppe outposts determined by local climatic, topographic, and edaphic conditions. In the extrazonal steppes, in particular within the Anatolian, Danubian, Thracian, and Pannonian grasslands, it is more or less continuously distributed, but with several disjunct occurrences in the central Balkan Peninsula, which is renowned for its high biodiversity. Several (infra)specific taxa have been recognised within E. glareosa s.l., but relationships among them remain elusive. We applied an integrative approach ranging from cytogenetics (relative genome size and ploidy estimation, chromosome counting) and morphometrics to phylogenetics (internal ribosomal transcribed spacer sequencing and amplified length polymorphism fingerprinting), with geographic focus on the central and eastern Balkan Peninsula. We inferred multiple polyploidisations within the group and complex phylogenetic patterns. We uncovered cryptic lineages in the central Balkan Peninsula, where the description of two new species, diploid E. balcanica, and tetraploid E. skopjensis was necessary. In addition, we revealed high diversity, partly related to polyploidisations, among the populations from the eastern Balkan and Pontic steppes, likely pertaining to different species. Finally, the main phylogeographic split within E. glareosa is between (1) Pannonian, central and eastern Balkan populations, and (2) the easternmost Balkan, Pontic, and Anatolian populations. Our results thus highlight the outstanding conservation value of the extrazonal European steppes that are not just an outpost of zonal Eurasian steppes. We also point to the remarkable biodiversity of the central and eastern Balkan Peninsula and the need for further in-depth studies of this biodiversity hotspot.